Study on Acute Toxicity of Amiodarone New Complexes With Cyclodextrin - Ghiciuc, Cristina Mihaela; Shleghm, Maytham Razaq; Vasile, Cornelia; Tantaru, Gladiola; Creteanu, Andreea; Ochiuz, Lacramioara (Frontiers in Pharmacology, 2021)
Amiodarone low solubility and high permeability is the limiting step for its bioavailability, therefore new formulations are needed to improve the solubility of amiodarone either to increase its oral bioavailability or to reduce its toxic effects. Complexation of amiodarone with cyclodextrin results in improved dissolution rate, solubility, and allows for a more controlled drug release. We characterized the acute toxicity of a new amiodarone 2-hydroxypropyl-β-cyclodextrin complex (AMD/HP-β-CD) as powdered form and as a matrix based on Kollidon® and chitosan, administered intraperitoneally in laboratory animals. There were developed two formulations of matrix: one containing only pure AMD as a control sample (Fc) and one containing the inclusion complex with the optimal solubility (F). AMD was equitoxic with HP-β-CD after intraperitoneal administration (289.4 mg/kg for AMD and 298.3 mg/kg for AMD/HP-β-CD), with corresponding histopathological changes. The matrix based formulations presented higher LD50 values for acute toxicity, of 347.5 mg/kg for Fc and 455.6 mg/kg for F10, conducting to the idea of a safer administration because KOL and CHT matrix modified the solubility and controlled the AMD release. The LD50 is 1.5 higher for AMD/HP-β-CD included in a KOL and CHT based matrix compared to the pure AMD, administered intraperitoneally.